Computer‐guided implant surgery and full‐arch immediate loading with prefabricated—metal framework—provisional prosthesis created from a 3D printed model. Issue 3 (20th February 2019) - Lanis, Alejandro; Alvarez del Canto, Orlando; Barriga, Patricio; Polido, Waldemar Daudt; Morton, Dean
Abstract: Objective: In this article, we describe the planning phase and clinical procedure where a CAD CAM 3D printed master model was utilized to create a prefabricated—titanium reinforced—fixed provisional prosthesis for a full‐arch immediate loading after computer‐guided implant placement. Clinical Considerations: The clinical procedure should be performed based on digital planning through an advanced surgical planning software and following the guidelines of full‐arch immediate loading protocol. The fact that the master model is fabricated under a computer‐assisted design and computer‐assisted manufacturing approach before implant placement makes the whole process considerably easier, faster, more precise and cheaper. Conclusions: The use of a prefabricated—metal framework—provisional prosthesis for full‐arch immediate loading created from a 3D printed master model seems to be a predictable treatment option when computer‐guided implant surgery is performed. Clinical Significance: The presented article described an interesting and innovative technique to optimize implant treatment based on digital technologies and 3D printing. The presented technique will help to diminish treatment costs and times especially for immediate loading procedures in fully edentulous patients because it allows to fabricate a prosthetic structure prior implant placement based on a 3D printing process.